2019
DOI: 10.14311/mad.2019.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Capturing and Delivering Value in the Trans-Atlantic Air Travel Market: The Case of the Air France-KLM, Delta Air Lines, and Virgin Atlantic Airways Strategic Joint Venture

Abstract: <p class="keywords">This paper presents a case study of the Air France-KLM, Delta Air Lines, and Virgin Atlantic transatlantic joint venture, one of the world’s largest strategic passenger joint ventures. The study used a qualitative research approach. The data gathered for the study was examined by document analysis. The strategic analysis of the joint venture was based on the use of Porter’s Five Forces Model. The study found that the joint venture has evolved over time through the addition of KLM Roya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…finding is consistent withBaxter (2018), who found that the Air France-KLM, Delta Airlines, and Virgin Atlantic joint venture delivered analogous synergetic value. At the outset of the strategic alliance in 1996, there was need for capital injection and management skills to enhance the performance of KQ.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…finding is consistent withBaxter (2018), who found that the Air France-KLM, Delta Airlines, and Virgin Atlantic joint venture delivered analogous synergetic value. At the outset of the strategic alliance in 1996, there was need for capital injection and management skills to enhance the performance of KQ.…”
supporting
confidence: 91%
“…Airlines interact through various kinds of alliances, such as joint ventures, mergers and acquisitions, and codeshare for marketing merits (Bamberger, Carlton, and Neumann 2004), with goals such as deterring competition and new entrants (Chen and Ross 2000), and efficiency rationale (Brueckner and Spiller 1991), pooling resources, and risk diversification. (Baxter 2018).…”
Section: Knowledge Transfer In the Airline Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Oslo opened a new airport at Gardermoen, a redundant military airfield, in 1998 replacing the bustling, compact Oslo Fornebu Airport. The new airport related high-speed train and improved road system to the airport cost almost NOK 20 billion ($USD 3 billion) [63]. Oslo Airport Gardermoen (OSL) is Norway's major airport and air traffic hub.…”
Section: A Brief Overview Of Oslo Airport Gardermoenmentioning
confidence: 99%